Pengaruh Tingkat Kecukupan Modal, Risiko Bisnis, dan Ukuran Perusahaan terhadap Nilai Perusahaan dengan Profitabilitas Sebagai Variabel Moderating pada perbankkan dari Tahun 2019-2021 - Aji Dwi Ardyansyah; Atwal Arifin (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study aims to analyze the effect of the capital adequacy ratio, business risk, and company size on firm value with profitability as a moderating variable for banking companies listed on the IDX for 2019-2021. The research population is all banking companies and the selected sample is 81 companies. The secondary data used in this study were taken from the Indonesian Stock Exchange website. The analysis technique uses multiple linear regression. The results of the study partially show that the capital adequacy ratio and business risk have no effect on firm value, while firm size has an effect on firm value. Moderation results show that the capital adequacy ratio and firm size have an effect on firm value which is moderated by profitability, while business risk has no effect on firm value which is moderated by profitability.